THE EFFECT OF COMBINATION OF KCl AND BANANA PEEL COMPOST ON THE GROWTH AND YIELD OF TOMATO ON ALLUVIAL SOIL - RIPAWATI, RIPAWATI; SAFWAN, MULYADI; NURJANI, NURJANI (Fakultas Pertanian Universitas Tanjungpura, 2018)
ABSTRAK The purpose of this study was to determine the best dose of the combination of KCl and Compost Banana Peel on the growth and yield of tomatoes on alluvial soil. This research was conducted from October 2017 to January 2018 at Trial Garden of Agriculture faculty Tanjungpura University. The research design used in this study was Completely Randomized Design with 6 levels of combination treatment of KCl and Compost Banana Peel: A = 3.1 g/polybag KCl + 0 Compost Banana Peel, B = 3.1 g/polybag KCl + 500 g/polybag Compost Banana Peel, C = 4.4 g/polybag KCl + 500 g/polybag Compost Banana Peel, D = 5.6 g/polybag KCl + 500 g/polybag Compost Banana Peel, E = 6.9 g/polybag KCl + 500 g/polybag Compost Banana Peel, F = 8.1 g/polybag KCl + 500 g/polybag Compost Banana Peel. Each treatment was repeated four times, and the experimental unit consisted of 4 plant samples. Variables in this study were plant height, root volume, dry weight, number of fruit per plant, fruit weight per plant and weight per fruit. The result of variety analysis shows that combination of KCl and Banana Peel Compost have significant effect on plant height, root volume, dry weight and not significant effect on number of fruit per plant, fruit weight per plant and weight per fruit, the result of this research show that combination 3,1 g/polybag KCl + 500 g/polybag Compos Banana Peel equalof20ton/hagive effektive growth and yield on tomato plant on alluvial soil. Keywords: Alluvial, Compost Banana Peel And KCl, Tomato.